Interconnections between apoptotic, autophagic and necrotic pathways: implications for cancer therapy development. Issue 1 (10th January 2013) - Jain, Mayur V.; Paczulla, Anna M.; Klonisch, Thomas; Dimgba, Florence N.; Rao, Sahana B.; Roberg, Karin; Schweizer, Frank; Lengerke, Claudia; Davoodpour, Padideh; Palicharla, Vivek R.; Maddika, Subbareddy; Łos, Marek
Summary The rapid accumulation of knowledge on apoptosis regulation in the 1990s was followed by the development of several experimental anticancer‐ and anti‐ischaemia (stroke or myocardial infarction) drugs. Activation of apoptotic pathways or the removal of cellular apoptotic inhibitors has been suggested to aid cancer therapy and the inhibition of apoptosis was thought to limit ischaemia‐induced damage. However, initial clinical studies on apoptosis‐modulating drugs led to unexpected results in different clinical conditions and this may have been due to co‐effects on non‐apoptotic interconnected cell death mechanisms and the 'yin‐yang' role of autophagy in survival versus cell death. In this review, we extend the analysis of cell death beyond apoptosis. Upon introduction of molecular pathways governing autophagy and necrosis (also called necroptosis or programmed necrosis), we focus on the interconnected character of cell death signals and on the shared cell death processes involving mitochondria (e.g. mitophagy and mitoptosis) and molecular signals playing prominent roles in multiple pathways (e.g. Bcl2‐family members and p53). We also briefly highlight stress‐induced cell senescence that plays a role not only in organismal ageing but also offers the development of novel anticancer strategies. Finally, we briefly illustrate the interconnected character of cell death forms in clinical settings while discussing irradiation‐induced mitotic catastrophe. The signalling pathways are discussed in their relation to cancer biology and treatment approaches.